Pengaruh kerapatan vegetasi dan kerapatan bangunan terhadap bencana banjir dan longsor di area perkotaan - Valeria Theresia Woy; Rieneke Lusia Evani Sela; Ingerid Moniaga; Andy Anton Mangopa Malik (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Rapid urban development increase building density at the expense of vegetation. When urban areas become less green and more concrete, environmental problems such as floods and landslides are likely to occur. This study aimed to investigate the changes in vegetation and building density in Wenang and Wanea Districts over 8 years based on Landsat imagery using ArcGIS tools. Methods such as the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-Up Index (NDBI) were used to analyze the impact of these effects on floods and landslides. From the results, vegetation density declined while building density increased over 8 years. These changes influenced floods and landslides based on the magnitude of vegetation and building indices. For instance, areas with higher building indices became more prone to flooding while those with higher vegetation indices were susceptible to landslides.